Study of productive processes of a farm on the municipality of Rio Grande, on Southern Brazil (Caderno de Ciências Agrárias, 2017)
The producers must achieve a management degree that allows the evaluation of the economic return from the propriety and the activities involved in it, making it possible by the data analysis to obtain information which enables technical decisions. The objective of this study is to evaluate the costs of production and its productive procedures to support the producer when taking decisions and seeking for improvements. The work was done in a rural propriety where are performed several activities. Data collection started on July 1st of 2009 and ended on June 31st of 2010. There were evaluated the following items: gross margin of the property and of the different processes; depreciation; average cost; investment return and profitability. Fixed, variables, operational and opportunity costs were also identified. Most productive processes typified operational costs, but did not pay off the economic costs, the Angus breeding could settle the total economic cost, since the raising of Criollo horses does not cover variable costs. It was noticed that the profitability of the macro productive process was positive. The cost of capital opportunity demonstrated that the property should develop a strategic plan to increase their productive rates in the different agricultural activities.